Pengaruh Kepemimpinan, Budaya Organisasi dan Kecerdasan Emosional melalui Kepuasan Kerja terhadap Kinerja guru (Studi pada SMP Negeri Simpang Mamplam Kabupaten Bireuen) - Rahmadani, Rahmadani; Fauzi, Fauzi; Mirja, Mirja (Singkite Journal, 2024)
The research aims to analyze: a) the relationship between head leadership, organizational culture and teacher emotional intelligence which influences performance, b) the influence of head leadership, organizational culture and emotional intelligence partially or simultaneously on teacher performance through job satisfaction. This research uses quantitative descriptive methods with inferential analysis. This research took a study of 81 teachers in public junior high schools in Simpang Mamplam sub-district, Bireuen Regency. The results of the path analysis show that the influence of Principal Leadership on teacher job satisfaction is 28.37%. There is an influence of Organizational Culture on teacher job satisfaction of 8.02%. There is an influence of emotional intelligence on teacher job satisfaction of 12.87%. Job satisfaction also influences teacher performance by 77.44%. The influence of the principal's leadership on teacher performance through job satisfaction is 38.54%. The influence of organizational culture on teacher performance through job satisfaction is 15.92%. There is an influence of teacher emotional intelligence on teacher performance through job satisfaction of 20.32%. Together, the influence of leadership, organizational culture and emotional intelligence on teacher job satisfaction is shown by the determination value between these variables, which is 47.4%.